AIDS means business too - McLaren, Les; Parr, Adrienne; Oxenham, Heather; Plain, Andrew (Health Media for the AIDS Bureau, N.S.W. Dept. of Health, 1989)
Video provides basic information about AIDS, but designed principally to highlight AIDS issues relevant to workplaces throughout Australia. Raises for discussion issues of workplace risk, disclosure of HIV/AIDS status, privacy, insurance, first aid, confidentiality, occupational safety and discrimination.